1998
DOI: 10.1086/301935
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Imprinting Defects in Prader-Willi Syndrome and Angelman Syndrome: Implications for Imprint-Switch Models, Genetic Counseling, and Prenatal Diagnosis

Abstract: The Prader-Willi syndrome (PWS) and the Angelman syndrome (AS) are caused by the loss of function of imprinted genes in proximal 15q. In approximately 2%-4% of patients, this loss of function is due to an imprinting defect. In some cases, the imprinting defect is the result of a parental imprint-switch failure caused by a microdeletion of the imprinting center (IC). Here we describe the molecular analysis of 13 PWS patients and 17 AS patients who have an imprinting defect but no IC deletion. Heteroduplex and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 50 publications
3
107
0
2
Order By: Relevance
“…(2) The aberrant VHL hypermethylation in UOK 121 cells may not be caused by mutation at all and therefore represent a`spontaneous'`epigenetic' type cis-defect. This defect could be similar in nature to the imprinting defect in a small subset of sporadic cases of Prader-Willi and Angelman syndromes that was never observed in hereditary forms (BuÈ rger et al, 1997;Buiting et al, 1998). In these cases the imprinting center is not mutated and some of the patients share the paternal (Prader-Willi) or the maternal (Angelman syndrome) haplotype with an una ected sib.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…(2) The aberrant VHL hypermethylation in UOK 121 cells may not be caused by mutation at all and therefore represent a`spontaneous'`epigenetic' type cis-defect. This defect could be similar in nature to the imprinting defect in a small subset of sporadic cases of Prader-Willi and Angelman syndromes that was never observed in hereditary forms (BuÈ rger et al, 1997;Buiting et al, 1998). In these cases the imprinting center is not mutated and some of the patients share the paternal (Prader-Willi) or the maternal (Angelman syndrome) haplotype with an una ected sib.…”
Section: Discussionmentioning
confidence: 68%
“…For instance, in mouse cells reversible heterochromatinization can be promoted by some nickel compounds which can interact directly with histone H1 and induce local de novo methylation which is stable (Lee et al, 1995). Interestingly,`epimutations' are now considered a possible factor, which may cause imprinting defects in some sporadic Prader-Willi and Angelman syndrome cases (BuÈ rger et al, 1997;Buiting et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…64,65 AS is usually associated with genetic abnormalities at an imprinted cluster containing UBE3A within 15q11-q13, and approximately 2-4% of the patients show epigenetic defects at this region, which include loss of methylation at the ICR at an imprinted bicistronic transcript encoding small nuclear ribonucleoprotein N (SNRPN) and SNRPN upstream reading frame (SNURF) (referred to as SNRPN) (Figure 2 and Table 1). [66][67][68] Among those, 92% are thought to have epigenetic mutations occurring in either oocytes or early embryos. 66 Maternally transmitted deletions of a region located 35 kb upstream of the SNRPN ICR, along with loss of methylation, have been identified in AS patients, which led to the discovery of the AS-imprinting center.…”
Section: Childhood Diseases Associated With Imprint Establishment or mentioning
confidence: 99%
“…It is thought that in this latter group imprinting defects are caused by spontaneous pre-or postzygotic events. 37 A recent report by Cox et al 38 has suggested that intracytoplasmic sperm injection may be a mechanism which interferes with establishment of the maternal imprint in an oocyte and might therefore predispose to Angelman syndrome. Among the group of patients where imprinting centre deletions have been detected, there are several familial cases.…”
Section: Genetics Of Angelman Syndromementioning
confidence: 99%